2015
DOI: 10.1097/prs.0000000000000999
|View full text |Cite
|
Sign up to set email alerts
|

The Newborn Butterfly Project

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 15 publications
1
41
1
1
Order By: Relevance
“…Our research indicated that the total treatment duration for constricted ears was 10.33 ± 3.44 weeks; this treatment period included the expanding duration (8.54 ± 2.98 weeks) and consolidation duration (1.67 ± 1.56 weeks), which were much longer than those required for other deformities. 9 , 14 , 15 This prolonged treatment duration is required mainly because constricted tension caused by skin and cartilage deficiencies necessitates a prolonged treatment duration for long-lasting expansion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research indicated that the total treatment duration for constricted ears was 10.33 ± 3.44 weeks; this treatment period included the expanding duration (8.54 ± 2.98 weeks) and consolidation duration (1.67 ± 1.56 weeks), which were much longer than those required for other deformities. 9 , 14 , 15 This prolonged treatment duration is required mainly because constricted tension caused by skin and cartilage deficiencies necessitates a prolonged treatment duration for long-lasting expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Complication rates of tissue excoriations and breakdown range from 3% to 7.6% for molding of ear abnormalities. 5,9,11,14 In our study, this rate was 9.8% and included skin excoriations and pressure ulcers. The relatively higher rate of tissue excoriations and dermatitis [11% (10 of 91)] may have been associated with the tissue tension and a relatively longer treatment time.…”
Section: Complicationsmentioning
confidence: 93%
“…Nonsurgical methods, such as splinting or rigid ear molding, take advantage of the plasticity of auricular cartilage during the neonatal period, correcting the deformity over the first month of life 5 . Early identification of ear deformity is crucial for the success of non-invasive ear molding 7 . At birth, high levels of circulating maternal estrogens result in increased levels of hyaluronic acid in ear cartilage, which increases the ear’s malleability and plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…The ear-molding technique was first described in the 1980s by Kurozumi et al [ 4 ], who reported the successful correction of constricted ear deformities by splinting the ear with foam. This technique has been shown to be effective for correcting ear deformities during the neonatal period [ 5 6 7 8 9 10 11 12 ]. The advantages of ear molding over otoplasty include fewer complications and a lower potential for psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…Byrd et al [ 5 ] contended that outcomes were clearly improved by initiating molding in neonates within the first 5–7 days, as results were suboptimal after 3 weeks of life. Doft et al [ 6 ] similarly found that the period of molding could be reduced to 2 weeks if initiated within the first week of life.…”
Section: Introductionmentioning
confidence: 99%